1992
DOI: 10.1042/bj2880137
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of activation of Na+/H+ exchange in human osteoblast-like SaOS-2 cells

Abstract: Because of the importance of pH homeostasis in bone and the current uncertainty about the mechanisms by which intracellular pH (pHi) is regulated in this tissue, we have investigated the roles of cytosolic free Ca2+ concentrations ([Ca2+]i) and protein kinase C on the activation of Na+/H+ exchange in human osteoblast-like SaOS-2 cells. [Ca2+]i and pHi were measured using Fura-2 and 2'7'-bis(2-carboxyethyl)-5(6)-carboxyfluorescein (BCECF) respectively. The basal pHi in HCO3(-)-free buffer was 7.36 +/- 0.04 unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
(25 reference statements)
1
6
0
Order By: Relevance
“…Our results add to the understanding of transduction mechanisms that mediate the NE‐mediated increase in Na + /H + exchange activity in rat pinealocytes. In support of the established link between elevation of [Ca 2+ ] i and activation of the Na + /H + exchange (Berk et al, 1987; Graham and Tashjian, 1992), we now confirm the importance of elevation of [Ca 2+ ] i in the NE‐mediated elevation of pH i . This is based on the observations that pretreatment with BAPTA‐AM is effective in blocking the NE‐mediated elevation of pH i .…”
Section: Discussionsupporting
confidence: 89%
“…Our results add to the understanding of transduction mechanisms that mediate the NE‐mediated increase in Na + /H + exchange activity in rat pinealocytes. In support of the established link between elevation of [Ca 2+ ] i and activation of the Na + /H + exchange (Berk et al, 1987; Graham and Tashjian, 1992), we now confirm the importance of elevation of [Ca 2+ ] i in the NE‐mediated elevation of pH i . This is based on the observations that pretreatment with BAPTA‐AM is effective in blocking the NE‐mediated elevation of pH i .…”
Section: Discussionsupporting
confidence: 89%
“…The additive effects of ionomycin and PMA further support the independent pathways for Na+/H+ exchange activation by the two drugs. In a human U937 cell line, a similar additive effect of calcium and PKC on Na+/H+ exchange has been described (Alvarez et al, 1989), whereas others have shown partial additivity between these two pathways in acidified cells only (T6rnquist & Tashjian, 1992; Graham & Tashjian, 1992).…”
Section: Intracellular Phmentioning
confidence: 73%
“…To ensure that the Na ϩ -free BSS effectively inhibited Na ϩ /H ϩ exchange, SaOS-2 cells were loaded with the pH-sensitive fluorescent probe BCECF/AM and then acidified with 1 M nigericin (a K ϩ /H ϩ ionophore). In nigericin-acidified SaOS-2 cells, PMA induces alkalinization via a Na ϩ /H ϩ exchanger-dependent mechanism (42). This PMA-induced alkalinization was completely blocked in Na ϩ -free buffer (data not shown).…”
Section: Role Of Na ϩ /H ϩ Exchange In the Pth-induced Increase In Ecar-mentioning
confidence: 90%